IMPLEMENTASI STRATEGI BAURAN PEMASARAN DALAM MEMASARKAN PRODUK APLIKASI AKUNTANSI BERBASIS DIGITAL EDUKASI: FINANCIAL REPORT ASSISTANT (FIRA) - Ningrum, Ira Sita; Syah, Tantri Yanuar Rahmat; Hamdi, Edi; Munandar, Agus; Sita Ningrum, Ira (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
The accounting system is a field that handles the planning and application of procedures for collecting and reporting financial data—planning a system with elements of checking and matching (checks & balances) to maintain company assets and have an efficient and beneficial information flow for management. The process of making financial statements seems complicated, especially there are still some small businesses that do not understand how to make their financial statements as an opportunity for accounting application providers to help small entrepreneurs by presenting easy and real-time accounting applications, as well as with the support of up-to-date technology. Financial Report Assistant (FIRA) is here to answer the problems of small entrepreneurs as an accounting application solution with service features that integrate all the company's accounting administrative needs in terms of financial records, calculation of income tax liabilities, budgeting, per-project financial statements to financial health analysis whose superior features can be selected and adjusted to consumer needs. With the Ask The Expert feature, customers don't have to worry about the FIRA accounting application not functioning optimally, because consumers will be accompanied by a professional, friendly and ready to help facilitate consumer accounting administration work that can provide insights so that consumer businesses are more profitable, growth and sustained. The purpose of this study is to determine marketing strategies to make the right marketing mix strategy decisions in accordance with company goals. The method used in this study uses qualitative methods with SWOT analysis to find out strengths, weaknesses, opportunities, and threats. After conducting a SWOT analysis can provide an overview of the process needed to develop a strategy for implementing the marketing mix in marketing a product.